2009
DOI: 10.1128/cvi.00320-08
|View full text |Cite
|
Sign up to set email alerts
|

RelB Sustains IκBα Expression during Endotoxin Tolerance

Abstract: Transcription factors and chromatin structural modifiers induce clinically relevant epigenetic modifications of blood leukocytes during severe systemic inflammation (SSI) in humans and animals. These changes affect genes with distinct functions, as exemplified by the silencing of a set of acute proinflammatory genes and the sustained expression of a group of antimicrobial and anti-inflammatory genes. This paradigm is closely mimicked in the THP-1 human promonocyte cell model of lipopolysaccharide (LPS) endotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…As mentioned previously, opening the chromatin at target genes during this acute phase involves histone phosphorylation and acetylation. However, sustained exposure to LPS or subsequent LPS challenge activates a pathway leading to permanent gene repression, as characterized for TNF-a and IL1-b (El Gazzar et al 2008;Chen et al 2009). This relies on a change in the composition of NF-kB transcription factor at the proximal promoters of TNF-a and IL1-b, with a shift from activating p65-p50 to repressive RelB-p50, owing to the up-regulation of RelB expression by p65-p50.…”
Section: The Epigenetic Component Of Severe Systemic Inflammation Andmentioning
confidence: 99%
“…As mentioned previously, opening the chromatin at target genes during this acute phase involves histone phosphorylation and acetylation. However, sustained exposure to LPS or subsequent LPS challenge activates a pathway leading to permanent gene repression, as characterized for TNF-a and IL1-b (El Gazzar et al 2008;Chen et al 2009). This relies on a change in the composition of NF-kB transcription factor at the proximal promoters of TNF-a and IL1-b, with a shift from activating p65-p50 to repressive RelB-p50, owing to the up-regulation of RelB expression by p65-p50.…”
Section: The Epigenetic Component Of Severe Systemic Inflammation Andmentioning
confidence: 99%
“…In SSI, the activator p65 targets TNF ␣ and IL-1 ␤ and feeds forward to induce RelB as an activator of a distinct target module, e.g. I B inhibitor-␣ (I B ␣ ) [22] . Thus, these two feedforward loops from p65 generate RelB as a dual-function mediator of distinct targets with different functions and provide one essential mechanism for gene-specific programming that requires integrating transcription factors with epigenetic histone and DNA modifiers.…”
Section: Feed-forward Loopsmentioning
confidence: 99%
“…We discovered that de novo induction of NF-B transcription factor RelB after TLR4 stimulation is necessary and sufficient for silencing transcription of TNF␣ and IL-1␤ in the SSI phenotype (8,19). We also found that RelB can function in the same cell type as a dual transcription regulator in the SSI phenotype to deactivate transcription of acute proinflammatory genes while activating transcription of the NF-B regulator IB␣ (20). RelB also participates in constitutive silencing of inflammatory genes in fibroblasts by a process that supports regional methylation of CpG DNA (21), and when normally silenced fibroblasts are rendered RelB Ϫ / Ϫ , they become responsive to LPS (22).…”
mentioning
confidence: 93%